Konseling Pasca Face Reading Untuk Meningkatkan Self Accaptance Calon Pengantin - Azmi, Irsad Roxiyul (Jurusan Bimbingan dan Konseling Islam, 2018)
Personality is an important instrument in creating familyharmony. While cases of divorce are increasing, divorce is caused bydifferences in personality that is not understood, so they feel unsuitable, thendivorce occurs. The researcher used a qualitative research method type ofcase study. The study intends to find the theory of face reading, which is usedas an instrument of measurement tools in counseling aimed at increasing theself-acceptance of prospective wives. Furthermore, a case study wasconducted to apply the counseling concept that had been found in a realcounseling setting with the counselee of a prospective wife. At this stage thedata is obtained through interviews and observations from clients. In thisresearch it was categorized as quite successful, with a percentage of 70%. Thesuccess is evidenced by changes in the attitude of the client in the form of: theclient knows the personality of his partner, the client understands how torespond to his partner, the client knows the lack of partners and findsolutions, clients know the potential and know how to develop it, clients findways to become ideal families, clients rarely complain about the personality ofhis partner.